Fasilitasi Pendampingan Kelembagaan Koperasi Kelurahan Merah Putih (KKMP) Di Kelurahan Semarang Barat Kota Semarang - Damayanti, Dina; Werdiningsih, Rini; Nurkholik, Nurkholik; Sulandjari, Rekno; Ulfa, Firda Nisafera (Annusfy : Journal of Multidisciplinary Research, 2025)
The community service activities aim to provide institutional facilitation and mentoring through training, managerial development, strengthening organizational structures, and developing business development strategies for cooperatives. The methods used include interactive lectures, Focus Group Discussions (FGDs), Problem-Based Learning, and Annual Member Meeting (RAT) simulations. The results of the activities indicate an increase in the understanding of management and members regarding cooperative governance, business planning, service innovation, and cooperative decision-making mechanisms. This mentoring is expected to be the first step in strengthening the Merah Putih Village Cooperative (KKMP) so that it can develop into a healthy, accountable cooperative that contributes to the welfare of the West Semarang Village community